1987
DOI: 10.1115/1.3248137
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation in Convective Heat Transfer and Isothermal Convective Mass Transfer

Abstract: The irreversible generation of entropy for two limiting cases of combined forced-convection heat and mass transfer in a two-dimensional channel are investigated. First, convective heat transfer in a channel with either constant heat flux or constant surface temperature boundary conditions are considered for laminar and turbulent flow. The entropy generation is minimized to yield expressions for optimum plate spacing and optimum Reynolds numbers for both boundary conditions and flow regimes. Second, isothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…They compared their expressions by those previously obtained by Bejan 12 and San et al 14,15 22 analyzed entropy creation due to laminar forced convection in the entrance region of concentric annulus. They found that raising the Eckert number causes an increase in entropy production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They compared their expressions by those previously obtained by Bejan 12 and San et al 14,15 22 analyzed entropy creation due to laminar forced convection in the entrance region of concentric annulus. They found that raising the Eckert number causes an increase in entropy production.…”
Section: Introductionmentioning
confidence: 99%
“…The local and average conductive Nusselt numbers, indicating energy characterization of heat between the outlet wall and the moving fluid, are given in equations (15) and (16), respectively…”
Section: àKmentioning
confidence: 99%
See 1 more Smart Citation
“…The local volumetric rate of entropy generation, S gen (W/m 3 K), in the presence of viscous dissipation, heat transfer and mass transfer is given by [23][24][25]:…”
Section: Entropy Generation Analysismentioning
confidence: 99%
“…The entropy generation and its minimization are investigated by many researchers. Bejan 1,2 and San et al 3 are the first who proposed different analytical solutions for the entropy generation equation in several simple flow situations. They introduce the concept of entropy production number and irreversibility distribution ratio, presenting spatial distribution profiles of entropy generation.…”
Section: Introductionmentioning
confidence: 99%